Learning Among Neanderthals and Palaeolithic Modern Humans Archaeological Evidence - Nishiaki, Yoshihiro; Jöris, Olaf.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is based on the research performed for the Replacement of Neanderthals by Modern Humans Project. The central issue of the project is the investigation of possible differences between the two populations in cognitive ability for learning. The project aims to evaluate a unique working hypothesis, coined as the learning hypothesis, which postulates that differences in learning eventually resulted in the replacement of those populations. The book deals with relevant archaeological records to understand the learning behaviours of Neanderthals and modern humans. Learning behaviours are conditioned by numerous factors including not only cognitive ability but also cultural traditions, social structure, population size, and life history. The book addresses the issues in two parts, comparing learning behaviours in terms of cognitive ability and social environments, respectively. Collectively, it provides new insights into the behavioural characteristics of Neanderthals and modern humans from a previously overlooked perspective. Furthermore, it highlights the significance of understanding learning in prehistory, the driving force for any development of culture and technology among human society.
1. Learning Behaviors among Neanderthals and Paleolithic Modern Humans: An Introduction -- 2. Neural Underpinnings of Creative Thinking and Tool Use: A Meta-Analysis of Neuroimaging Data -- 3. The Expert Performance Model of Neanderthal Cognition -- 4. Cognitive Capacities of the Neanderthals -- 5. Mastering Hammer Use in Stone Knapping: An Experiment -- 6. Evidence for Neanderthal Hand-Preferences from the Late Middle Paleolithic Site of Buhlen, Germany: Insights into Neanderthal Learning Behaviour -- 7. Good and Bad Knappers Among Neanderthals -- 8. The Apprentice Core: Evidence from a Lithic Refitting at the Upper Paleolithic Site Kyushirataki-5 in Hokkaido, Northern Japan -- 9. Learning Behavior of Sanukite Knapping among the Upper Paleolithic communities of Suichoen, Japan -- 10. Strong Differences in Neanderthal and AMH cannot be Inferred from Ethnographic Evidence for Skill and Learning in Hunting -- 11. Marine shells from Tor Fawaz, southern Jordan, Southern Jordan, and Their Implications for Behavioral Changes from the Middle to Upper Paleolithic in the Levant -- 12. Modeling Learning Strategies and the Expansion of the Social Network in the Beginning of Upper Paleolithic Europe: Analysis by Agent-Based Simulation -- 13. Transculturation versus Acculturation: A Clarification -- 14. Ratchets and Replacement: The Potential Role of Cultural Accumulation in the Replacement of Neanderthals by Modern Humans.
Keywords: Anthropology; Archaeology; Ethnology; Anthropology; Archaeology; Sociocultural Anthropology